Goal-Based Construction of Preferences: Task Goals and the Prominence Effect - Fischer, Gregory W.; Carmon, Ziv; Ariely, Dan; Zauberman, Gal (Management Science, 1999)
Preferences inferred from choice are more likely to favor the alternative that is superior with respect to the prominent (most important or salient) attribute than are preferences inferred from matching (direct tradeoff) judgments. This prominence effect violates standard models of rational choice and complicates the task of measuring preferences. In this article, we propose a new task-goal hypothesisregarding the prominence effect: The prominent attribute receives more weight in tasks whose goal is to differentiate among options than in tasks whose goal is to equate options. We use this hypothesis to generalize the prominence effect beyond choice and matching to several additional tasks, including the choice-based matching and difference comparison methods that are widely employed in decision analysis. The results of three studies provide strong support for the task-goal account of the prominence effect and cast doubt on competing explanations. We discuss the implications of these findings for descriptive decision theory and for preference measurement in decision analysis, public policy, and marketing.